Ethnobotany and urban life: medicinal and food use of plants from Karachi (Pakistan’s largest metropolis) - Perveen, Anjum; Wei, Calvin R.; Bokhari, Syed Waleed Ahmed; Ijaz, Shabir; Iqbal, Javeed; Ashraf, Saima; Kousar, Shazia (Ethnobotany Research and Applications, 2024)
Background: Traditional medicines knowledge is more famous and well-documented in rural and remote areas in Pakistan and worldwide than in urban areas. A present effort was made to document the ethnobotanical practices among the communities of Karachi city and provide the basis for the development of natural drug discovery. Methods: For ethnobotanical data collection, 177 local informants and traditional healers were interviewed. Various quantitative indices such as the relative frequency of citation (RFC), fidelity level (FL), use value (UV), and the Jaccard Index (JI) were applied to the documented data. Results: The traditional medicinal uses of 97 plant species belonging to 47 families were reported. Solanaceae (seven taxa) was followed by Boraginaceae and Fabaceae (six taxa each), Cucurbitaceae (five taxa); Amaranthaceae, Convolvulaceae, Malvaceae, Verbenaceae, and Zygophyllaceae (four taxa each), which were the leading families that contributed the highest number of taxa. The highest plant-used parts were leaves, with 45 reports (28.84%), followed by fruit (15.38%). It was observed that the majority of species were used to treat stomach problems, respiratory issues, general wellness, skin conditions, liver-related conditions, and fever, respectively. Conclusion: Ethnomedicinal findings reported in this study offer concrete proof of the use of therapeutic plants by residents of Karachi city. The research also showed that the medicinal plants in the region constitute a significant source of herbal medicines used to treat various ailments. This survey can serve as a starting point for future scientific research aimed at creating new plant-based pharmaceuticals for the market. Keywords: Ethnobotany; Karachi, Sindh, Human diseases, Herbal medicine